The discreet narrative of dissent: an analysis of Leila’s Brothers movie - Azeri Matin, Alireza (Faculty of Communications Science, Dr. Soetomo University, 2025)
Saeed Roustayi’s Leila’s Brothers (2022) sparked significant controversy in Iran following its international success, culminating in criminal charges against the movie’s director and producer. While public discourse largely focused on the film’s portrayal of poverty and patriarchy, this study goes beyond it and argues that its narrative structure subtly encodes a critique of the authoritarian regime in Iran. Applying classical structuralist models– Todorov’s three-act structure and Propp’s character archetypes, this research analysed how the film’s narrative mechanisms reflect dissent against entrenched authority. The study focused particularly on the portrayal of Esmail, the family’s patriarch, whose obsession with power and status parallels the perceived characteristics of Iran’s Supreme Leader. Through this allegorical construction, the narrative conveys a veiled political commentary that may explain the film’s censorship. Leila, the central character, challenges familial and societal norms, positioning her as a catalyst for change within a rigid system. The film’s closure, juxtaposing the quiet death of Esmail with a young girl’s birthday celebration, symbolises generational transition and the fading legitimacy of traditional power structures. While this analysis draws on classical structuralist models, it contextualises them within Iran’s contemporary sociopolitical environment. In particular, the film’s portrayal of gender, authority, and resistance reflects the ethos of the Woman, Life, Freedom movement. This study demonstrates how narrative structures, though seemingly neutral, can encode political dissent in contexts of censorship, offering new insights into resistance media in authoritarian settings.